In silico modeling of zerumbone as a multi-target therapeutic for lung disorders with experimental characterization of its purity and thermal stability - Nourhan Elsayed (Results in Chemistry, 2025)
Zerumbone (ZER), a bioactive sesquiterpene derived from Zingiber zerumbet, exhibits anti-inflammatory, antifibrotic, and anticancer properties, making it a promising candidate for lung disorder therapy. This study employs in-silico approaches to elucidate ZER’s molecular interactions with key inflammatory, fibrotic, and oncogenic targets, including TNF-α, TGF-β, IGF-1, and their receptors. Molecular docking analysis revealed that ZER acts as a reversible, non-covalent inhibitor of these proteins, potentially disrupting pathological signaling pathways. ADMET profiling demonstrated ZER’s favorable pharmacokinetic properties, supporting its suitability for pulmonary delivery. However, molecular docking also identified covalent interactions between ZER and hepatic (CYP1A2, CYP3A4, CYP2D6) and renal (SGLT2, renin) proteins, which may contribute to systemic toxicity. Protein-protein interaction (PPI) analysis highlighted TNF-α and TGF-β as key regulatory hubs in lung diseases, reinforcing ZER’s potential as a multi-target therapeutic agent. Analytical characterization using FTIR, GC-MS, TGA, and DSC confirmed ZER’s purity, chemical integrity, and thermal stability, further supporting its pharmaceutical application. Given its selective non-covalent binding to pulmonary targets and covalent modification of systemic proteins, inhalation therapy emerges as a preferable route to enhance ZER’s efficacy while minimizing off-target effects. Future in-vitro and in-vivo studies are warranted to validate these findings and optimize ZER’s formulation for targeted pulmonary delivery.